Нормативно-правові акти як джерела адміністративного права України - Хиля, Михайло Михайлович; Khylya, M. M. (Тернопіль : ТНЕУ, 2019)
Дисертація є одним із перших в Україні комплексних досліджень нормативно-правових актів в системі джерел адміністративного права. Результатом дослідження є комплекс теоретичних узагальнень, висновків, низка нових наукових положень, важливих для сучасної теорії адміністративного права. Зокрема, у роботі розкрито стан наукової розробки питань ролі та місця нормативно-правових актів системі джерел адміністративного права України; здійснено теоретико-правову характеристику системи джерел адміністративного права України; визначено поняття, ознаки, особливості нормативно-правових актів у системі джерел адміністративного права України; класифіковано нормативно-правові акти як джерела адміністративного права України; визначено основні вимоги, а також охарактеризовано порядок прийняття нормативно -правових актів; проаналізовано способи реалізації нормативно-правових актів як джерел адміністративного права України; розкрито ключові особливості нормативно-правових актів суб’єктів владних повноважень. У роботі уперше сформовано та охарактеризовано систему вимог до нормативно-правових актів в системі джерел адміністративного права (юридичні, лінгвістичні та технічні вимоги), а також запропоновано уніфікувати вимоги до різних за юридичною силою та природою правового регулювання нормативно-правових актів в спеціальному законі. The dissertation is one of the first in Ukraine complex researches of lega l acts in the system of sources of administrative law. The result of the study is a set of theoretical generalizations, conclusions, a number of new scientific provisions that are important for modern theory of administrative law.In particular, the paper describes the state of scientific development of issues of the role and place of regulatory legal acts in the system of sources of administrative law of Ukraine; the theoretical and legal characterization of the system of sources of administrative law of U kraine is carried out; concepts, features, features of normative -legal acts in the system of sources of administrative law of Ukraine are defined; classified legal acts as sources of administrative law of Ukraine; the basic requirements are defined, as wel l as the procedure for adoption of normative legal acts; ways of realization of normative legal acts as sources of administrative law of Ukraine are analyzed; the key features of the legal acts of the subjects of power are revealed. The paper first formulated and characterized the system of requirements for legal acts in the system of administrative law sources (legal, linguistic and technical requirements), and also proposed to unify the requirements for different legal force and the nature of legal regula tion of legal acts in a special law. The monographic researches considered in the dissertation testify to the lack of complex scientific development of substantive and procedural aspects of the issues of the place of normative legal acts in the system of s ources of administrative law of Ukraine. Establishing an effective regulatory system that can only be implemented in the presence of qualitatively formed legal acts is a prerequisite for overcoming gaps and insufficiently regulated legal relationships. Therefore, a conceptual and correct understanding of the role of legal acts in the system of sources of administrative law (as well as in the system of all public law science and legislation) will remain a priority for legal science, given the importance of t he consequences of rulemaking and their influence on state processes. These are the main areas of research that have become the methodological basis for the development of regulatory issues as sources of administrative law. These include: research into the problems of design and rulemaking efficiency; research of rulemaking activity of various public institutions; research into different types of sources of public law; study of the nature of the norms of law, which became the basis of legal acts; studies related to various aspects of implementation of legal acts as sources of administrative law, rulemaking process in the administrative and legal sphere.
Legal acts as sources of administrative law of Ukraine
Keywords: нормативно-правові акти; джерела адміністративного права; джерела права; суб’єкти владних повноважень; вимоги; реалізація; особливості нормативно -правових актів; regulatory acts; sources of administrative law; sources of law; subjects of power; requirements; implementation; peculiarities of regulatory acts